Chemical characterization, antimicrobial activity and cardiac effects in rat heart of the ethyl acetate fraction of Syzygium cumini (L.) Skeels (Research, Society and Development, 2023)
Plants are important sources of secondary metabolites responsible for various biological activities. In this research, was evaluated the effect action ethyl acetate fraction of Syzygium cumini leaves (Sc-AcOEt) in the antimicrobial activity, contractile and electrical effects in isolated rat hearts and the chemical characterization. Antimicrobial activity was assessed using the disk-diffusion method and the determination of the minimum inhibitory concentration. The contractile and electrical effects were tested using the Langendorf method. The chemical characterization was evaluated through quantification and HPLC analyzes. P. aeruginosa was not viable in any concentration of the fraction (MIC 0,125 mg/mL), while S. aureus showed a MIC of 0.5 mg/mL. K. pneumoniae and E. coli had the highest MIC (1 mg/mL). A reduction in LVDP was observed after heart perfusion with 0.1 mg/mL of Sc-AcOEt. No change was observed in the duration of systole and diastole at all concentrations and in the electrocardiographic parameters. Total phenols, total flavonoids and total flavonols contents of Sc-AcOEt, calculated from the respective calibration curves, were 21.556µg/mg AGE, 617.222µg/mg QE and 315,222µg/mg RE, respectively. In addition, the HPLC analysis of Sc-AcOEt showed the presence of gallic acid, quercetin-3-glucoside, naringin and myricetin as main components. Thus, the Sc-AcOEt has important antimicrobial and cardiac activities possibly due to its chemical constituents.